Kinerja Auditor di Masa Pandemi: Pengaruh Kepemimpinan, Motivasi dan Sistem Informasi Penggajian - Johannis, Angelina Adistya; Maria, Evi (Penerbit Goodwood, 2025)
Purpose: This study aims to provide empirical evidence on the impact of leadership style, work motivation, and payroll accounting information systems on auditor performance at Public Accounting Offices (KAP) in Semarang City during the COVID-19 pandemic. Methodology: This study employed a quantitative approach, collecting primary data through questionnaires distributed to 85 auditors across 29 KAPs in Semarang City and analyzing the data using multiple linear regression analysis. Results/findings: The findings indicate that Leadership style and work motivation significantly impact auditor performance, highlighting the role of effective leadership and intrinsic motivation in maintaining audit quality during periods of disruption. Conclusion: This study found that leadership and work motivation significantly influenced auditor performance during the pandemic, whereas the payroll information system had no effect. Limitations: This study is limited by potential respondent subjectivity bias in the questionnaire data and its focus solely on auditor performance during the pandemic, restricting generalizability over time. Contribution: This study serves as a reference for KAP in formulating effective strategies and policies to maintain and improve auditor performance.